Placebo Controlled Study on the Efficacy and Safety of Calcipotriol in the Treatment of Mild to Moderate Psoriasis (Medical Forum Monthly, 2024)
Background: Calcipotriol is a vitamin D analogue that has been used now a day as monotherapy in mild to moderate psoriasis. We have conducted a placebo-controlled clinical comparative study to assess the efficacy and safety of calcipotriol in the treatment of psoriasis.Objective: To assess the efficacy and safety of calcipotriol in comparison with placebo in patients with mild to moderate psoriasis.Study Design: Experimental Study Place and Duration of Study: This study was conducted in the Department of Pharmacology and Therapeutics, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre (JPMC), Karachi from January 2008 to March 2008.Materials and Methods: Sixty patients with mild to moderate psoriasis were enrolled after obtaining their informed written consent and were divided into two groups, A and B. Group-A was administered calcipotriol and Group-B was considered as placebo group for three months. The study parameter (Psoriasis Area and Severity Index, PASI) score was noted after every fifteen days (02 weeks) and were evaluated statistically at the end of the study period.Results: The significant changes in mean ± SEM values were noted for the efficacy of calcipotriol during the period from day 0 to day 90 in group-A (calcipotriol) v/s group-B (placebo). According to the statistical evaluation, a reduction in the symptoms of the disease was found up to 67.8% in group A, and 0.5% in group-B. The difference between the results of both groups was noted to be highly significant (P<0.001).Conclusion: Calcipotriol as monotherapy is observed to be significantly superior to placebo in terms of efficacy and safety in the treatment of psoriasis.